(Table 1) Total carbonate content of ODP Leg 134 samples - R Pamela Reid; Steven N Carey; Thomas Scott Staerker; Maria VS Ask (PANGAEA, 1994)
Depositional processes in the collision zone between the North d extquotesingleEntrecasteaux Ridge (NDR) and the New Hebrides Island Arc were investigated in post-cruise analyses of sediment and nannofossils from Sites 827, 828, and 829. Reexamination of cores and analysis of grain size, turbidite frequency, carbonate content, and clay mineralogy, together with new nannofossil age determinations, were used to revise shipboard lithostratigraphies and interpret the sedimentologic history recorded at each site. The results of our analyses show that sedimentation on the inner trench slope and the impinging NDR has been significantly affected by the collision process. Uplift associated with subduction of the NDR beneath the New Hebrides Island Arc resulted in the emergence of Espiritu Santo Island and created a robust source of epiclastic sediment for the forearc area. Distribution of this material into deeper water has been modulated by Pleistocene sea level changes, which have influenced the frequency and extent of turbidity currents. Sedimentation at individual sites reflects the interplay between sediment source availability, sea level changes, and tectonic displacements, which have translated local depositional environments both horizontally and vertically. The study also provides evidence that ridge sediment and trench fill deposits have been accreted onto the forearc slope and that thrust faulting of subducting ridge sediment has occurred preferentially in kaolinite-rich horizons.
Supplement to: Reid, RP et al. (1994): Sedimentology of the collision zone between the North d extquotesingleEntrecasteaux Ridge and New Hebrides Island Arc (Sites 827, 828, and 829). In: Green, HG; Collot, J-Y; Stokking, LB; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 134, 73-88, https://doi.org/10.2973/odp.proc.sr.134.005.1994